Manipulation of enhanced absorption with tilted hexagonal boron nitride slabs. (April 2018) - Wu, Xiaohu; Fu, Ceji
Highlights: A method for achieving greatly enhanced absorptivity in a broadband with tilted hexagonal boron nitride slabs is proposed. The physical mechanism for the enhanced absorptivity is elucidated. The effects of the slab number and the slab thickness on the enhanced absorptivity are highlighted. Abstract: The wavevector of electromagnetic wave propagation in a hexagonal boron nitride (hBN) slab can be controlled by tilting its optical axis. This property can be used to manipulate the absorption in a hBN slab. By carefully analyzing the dependence of the absorptivity of a thin hBN slab on the tilted angle of its optical axis, we propose a structure that can realize great absorptivity enhancement in a band by stacking hBN slabs of different tilted angles. Our numerical results show that the absorptivity of a structure made of 91 stacked hBN slabs can be achieved higher than 0.94 in the wavenumber range from 1367 to 1580 cm −1 when the tilted angles of the slabs are properly arranged. The strong absorption is attributed to the combination of impedance matching at the slab interfaces and enlarged wavevectors in the slabs. This work reveals a novel way to realize strong absorption with anisotropic materials for applications in areas such as thermal radiative energy harvesting and conversion.